2016
DOI: 10.1371/journal.pntd.0005076
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between HLA-A, B and DRB1 Alleles and Severe Fever with Thrombocytopenia Syndrome

Abstract: ObjectiveSevere fever with thrombocytopenia syndrome (SFTS) is an emerging hemorrhagic fever caused by a tick-borne bunyavirus (SFTSV) in East Asian countries. The role of human leukocyte antigen (HLA) in resistance and susceptibility to SFTSV is not known. We investigated the correlation of HLA locus A, B and DRB1 alleles with the occurrence of SFTS.MethodsA total of 84 confirmed SFTS patients (patient group) and 501 unrelated non-SFTS patients (healthy individuals as control group) from Shandong Province wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In that study, serum IL-1β of non-fatal group was significantly lower than fatal group in the acute phase of SFTS, but dramatically elevated in 50–150 days after onset of illness, exhibiting late IL-1β response in the convalescent phase of SFTS. The differences could be due to the patient cohorts used in the studies 39 or the viruses that may have different pathogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, serum IL-1β of non-fatal group was significantly lower than fatal group in the acute phase of SFTS, but dramatically elevated in 50–150 days after onset of illness, exhibiting late IL-1β response in the convalescent phase of SFTS. The differences could be due to the patient cohorts used in the studies 39 or the viruses that may have different pathogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…HLA alleles are highly variable in different individuals and are closely related to host immune response and the susceptibility to disease. The allele frequency distributions of HLA-A , HLA-B , and DRB1 between two cohorts (patients with SFTS: n = 84; healthy individuals: n = 501) from Shandong Province, China, were analyzed, and it was found that haplotype A*02-B*15-DRB1*04 was positively associated with SFTSV susceptibility, whereas HLA-A*30, HLA-B*13 and haplotype A*30-B*13 , A*30-B*13-DRB1*07 had negative correlation with SFTS susceptibility ( Ding et al., 2016 ).…”
Section: Host Genetic Factorsmentioning
confidence: 99%
“…Therefore, the alleles encoding the amino acid sequences in HLA directly affect the susceptibility to certain diseases, e.g., H1N1 influenza (HLA-A*11, DRB1*10, HLA-B*35) [ 10 ], dengue infection (HLA-B*51, HLA-B*52, HLA-B*46) [ 11 ], AIDS (HLA-B*52) [ 12 ], etc. [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The loci A, B, C (class I) and loci DRB1, DQB1, and DPB1 (class II) of HLA genes are the most variable among all HLA genes, which determines their different affinity for the same antigen [ 15 ]. Furthermore, the linkage disequilibrium between alleles within a locus, as well as the haplotype frequencies within a population, may have a cumulative effect on antigen presentation [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%